Identifying common genetic etiologies between iridocyclitis and related immune-mediated diseases - Liu, Zhao; Zhang, Wenqiao; Wang, Qiuyuan; Du, Xumei; Tao, Zhiqi; Huang, Jianguo; Wang, Yuqin (Frontiers in Immunology, 2026)
BackgroundPatients with iridocyclitis are at heightened risk for immune-mediated diseases. The genetic underpinnings of iridocyclitis are intricate, necessitating an integrated approach to unravel the genetic connections between iridocyclitis and these diseases.MethodsGWAS data were integrated from three databases using METAL. Independent risk loci were analyzed through conditional and joint genome-wide multi-trait analysis, multi-marker genomic annotation, and functional mapping of significant loci. This approach combined quantitative trait loci data and various methodologies to identify genes and proteins associated with risk. Target gene verification was conducted through cell experiments and flow cytometry.ResultsThe study identified five independent iridocyclitis-related risk loci and 123 associated genes. Additionally, 14 multi-disease risk genes and 109 disease-related proteins were discovered. Flow cytometry confirms that FBXL18 and IL15RA are responsive to inflammatory stimuli and supports their role in immune-mediated pathways relevant to iridocyclitis, underscoring its potential as a therapeutic target.ConclusionThis study indicates that the polygenic factors shared between iridocyclitis and immune-mediated diseases are broadly distributed across the genome. These findings affirm a genetic link between iridocyclitis and immune-mediated diseases and highlight new therapeutic targets for these conditions.